ANALYSIS OF FACTORS DEPENDING INNOVATIVE ACTIVITY OF ORGANIZATIONS OF MOSCOW REGION - Svetlana N. Zhuravlev (Статистика и экономика, 2016)
The article gives a detailed analysis ofthe views of the organizations surveyedby economic activity. Due to the fact that the share of the manufacturing sector ofthe Moscow region in 2012. It accountedfor 23.1% of the GRP it is advisable to start with the sector. Manufacturing in accordance with the approved classiﬁcation are divided into high-tech (110 surveyed organizations), high-medium technology(259 organizations) and low-level andlow-tech.